The Weekend Effect in Information Releases: A Study of Earnings and Dividend Announcements - Damodaran, Aswath (Review of Financial Studies, 1989)
[Earnings and dividend announcements on Fridays are much more likely to contain reports of declines and to be associated with negative abnormal returns than those on other weekdays. While Friday reports elicit negative average returns for firms in all size classes, announcements by smaller firms have more negative returns associated with them on the following trading day, suggesting that they are more likely to release reports after close of trading or that prices adjust more slowly to the information in these reports. Nevertheless, a comparison of the average returns by weekday, with and without the Friday announcements, leads us to conclude that these announcements explain a surprisingly small proportion (3.4 percent) of the weekend effect.]